A Three-Component Model of the Control Error in Manual Tracking of Continuous Random Signals. (October 2013) - Gerisch, Hans; Staude, Gerhard; Wolf, Werner; Bauch, Gerhard
Objective: The performance of human operators acting within closed-loop control systems is investigated in a classic tracking task. The dependence of the control error (tracking error) on the parameters display gain, k display, and input signal frequency bandwidth, fg, which alter task difficulty and presumably the control delay, is studied with the aim of functionally specifying it via a model. Background: The human operator as an element of a cascaded human–machine control system (e.g., car driving or piloting an airplane) codetermines the overall system performance. Control performance of humans in continuous tracking has been described in earlier studies. Method: Using a handheld joystick, 10 participants tracked continuous random input signals. The parameters fg and k display were altered between experiments. Results: Increased task difficulty promoted lengthened control delay and, consequently, increased control error. Tracking performance degraded profoundly with target deflection components above 1 Hz, confirming earlier reports. Conclusion: The control error is composed of a delay-induced component, a demand-based component, and a novel component: a human tracking limit. Accordingly, a new model that allows concepts of the observed control error to be split into these three components is suggested. Application: To achieve optimal performance in control systems that include a human operator (e.g., vehicles, remote controlled rovers, crane control), (a) tasks should be kept as simple as possible to achieve shortest control delays, and (b) task components requiring higher-frequency (>1 Hz) tracking actions should be avoided or automated by technical systems.